Ni-Cr-Fe-Mo-BASED ALLOY HAVING EXCELLENT SURFACE CHARACTERISTICS, AND METHOD FOR MANUFACTURING THE SAME - OGASAWARA DAIKI; MIZUNO KENJI (2024)
To provide a Ni-Cr-Fe-Mo-based alloy with superior surface characteristics while regulating the composition of nonmetal inclusions that influence the surface characteristics, and a method for manufacturing the same.SOLUTION: A Ni-Cr-Fe-Mo-based alloy comprises, in mass%, C: 0.03-0.30%, Si: 0.05-1.50%, Mn: 0.05-2.00%, P: 0.05% or less, S: 0.005% or less, Cr: 18.0-28.0%, Mo: 6.0-15.0%, Cu: 1.0% or less, Al: 0.01-0.50%, Ti: 0.01-0.40%, Nb: 0.02-0.60%, Fe: 15.0-22.0%, Co: 0.5-4.0%, W: 0.10-2.00%, B: 0.0001-0.0100%, N: 0.005-0.100%, O: 0.0001-0.0060%, Mg: 0.0001-0.0300%, Ca: 0.0001-0.0080%, with the balance being Ni and inevitable impurities, wherein the composition of nonmetal inclusions 8a is regulated.SELECTED DRAWING: Figure 3 【課題】表面性状に影響を及ぼす非金属介在物の組成を制御し、表面性状に優れたＮｉ－Ｃｒ－Ｆｅ－Ｍｏ系合金およびその製造方法を提供する。【解決手段】質量％にて、Ｃ：０．０３～０．３０％、Ｓｉ：０．０５～１．５０％、Ｍｎ：０．０５～２．００％、Ｐ：０．０５％以下、Ｓ：０．００５％以下、Ｃｒ：１８．０～２８．０％、Ｍｏ：６．０～１５．０％、Ｃｕ：１．０％以下、Ａｌ：０．０１～０．５０％、Ｔｉ：０．０１～０．４０％、Ｎｂ：０．０２～０．６０％、Ｆｅ：１５．０～２２．０％、Ｃｏ：０．５～４．０％、Ｗ：０．１０～２．００％、Ｂ：０．０００１～０．０１００％、Ｎ：０．００５～０．１００％、Ｏ：０．０００１～０．００６０％、Ｍｇ：０．０００１～０．０３００％、Ｃａ：０．０００１～０．００８０％、残部がＮｉおよび不可避的不純物から成り、非金属介在物８ａの組成を制御したＮｉ－Ｃｒ－Ｆｅ－Ｍｏ系合金。【選択図】図３